2013
DOI: 10.1038/srep01053
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Arctic distributions of continental runoff in the Arctic Ocean

Abstract: Continental runoff is a major source of freshwater, nutrients and terrigenous material to the Arctic Ocean. As such, it influences water column stratification, light attenuation, surface heating, gas exchange, biological productivity and carbon sequestration. Increasing river discharge and thawing permafrost suggest that the impacts of continental runoff on these processes are changing. Here, a new optical proxy was developed and implemented with remote sensing to determine the first pan-Arctic distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
217
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(236 citation statements)
references
References 43 publications
(61 reference statements)
18
217
1
Order By: Relevance
“…The Lena (523 km 3 yr −1 ), Indigirka (54 km 3 yr −1 ), and Kolyma (48 km 3 yr −1 ) are the major rivers (Gordeev, 2006). During the ice-free season, the Lena plume can be traced in the outer shelf of the Laptev Sea (Fichot et al, 2013;Salvadó et al, 2016;Sánchez-García et al, 2011) while Pacific inflow from the Bering strait affects further east the East Siberia margin (Semiletov et al, 2005). The Pacific inflow exerts control on the nutrient balance as it supplies phosphorous and silicate to an otherwise nutrient-depleted region (Anderson et al, 2011;Semiletov et al, 2005).…”
Section: Study Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Lena (523 km 3 yr −1 ), Indigirka (54 km 3 yr −1 ), and Kolyma (48 km 3 yr −1 ) are the major rivers (Gordeev, 2006). During the ice-free season, the Lena plume can be traced in the outer shelf of the Laptev Sea (Fichot et al, 2013;Salvadó et al, 2016;Sánchez-García et al, 2011) while Pacific inflow from the Bering strait affects further east the East Siberia margin (Semiletov et al, 2005). The Pacific inflow exerts control on the nutrient balance as it supplies phosphorous and silicate to an otherwise nutrient-depleted region (Anderson et al, 2011;Semiletov et al, 2005).…”
Section: Study Regionmentioning
confidence: 99%
“…The land-derived material that does not settle in the coastal zone further travels across the continental margin reaching out to the outer-shelf region resuspended within the ben- thic nepheloid layer or in suspension within the surface river plume (Fichot et al, 2013;Sánchez-García et al, 2011;Wegner et al, 2003). Another fraction of terrestrial material can travel across the Siberian margin trapped in fast ice (Dethleff, 2005).…”
Section: Source Of the Pom (> 10 µM) Fractionmentioning
confidence: 99%
“…Previous studies have indicated that CDOM spectral slopes (particularly S 290−350 and S 275−295 ) can serve as indicators of DOM source and composition, where a steeper spectral slope typically suggests lower molecular weight material with decreasing aromatic content and a shallower (i.e., lower) slope typically suggests higher molecular weight material with increasing aromatic content (Green and Blough, 1994;Blough and Del Vecchio, 2002;Helms et al, 2008;Spencer et al, 2009a). Furthermore, S 275−295 has been identified as a reliable proxy for dissolved lignin and therefore terrigenous DOM supply across Arctic Ocean coastal waters, as well as photobleaching history (Helms et al, 2008;Fichot et al, 2013). We found a general increase in S 290−350 and S 275−295 moving downstream through the network, indicative of progressive photodegradation of DOM alongside likely reductions in average DOM molecular weight and aromaticity.…”
Section: Biogeosciencesmentioning
confidence: 99%
“…The riverine input can be monitored by optical methods with absorption, fluorescence, or remote-sensing measurements (Spencer et al, 2012;Walker et al, 2013;Fichot et al, 2013;Mann et al, 2016). The largest DOC concentrations were found in the Siberian rivers Lena -1300 µmol L −1 , Yenisey -842 µmol L −1 , and Ob -950 µmol L −1 , and the concentrations were lower in the North American Yukon -816 µmol L −1 and McKenzie -648 µmol L −1 rivers Mann et al, 2016).…”
Section: Relationship Between Cdom Absorption and Docmentioning
confidence: 99%